Assessing the impact of urban growth on air pollution: analysis of sentinel-5 satellites images using Google Earth engine - Kaushani Banerjee Bhaduri; Puja Samanta; Kasturi Mukherjee; Pratik Dash (Discover Geoscience, 2025)
Abstract Over the past four decades, India's rapid economic development, urban expansion, and unregulated industrialization have been major contributors to severe air pollution. This study aims to examine the relationship between various modes of urban growth and air pollution in Kolkata Urban Agglomeration (KUA), India's third-largest urban area. Using Google Earth Engine (GEE) and Sentinel-5P satellite data, concentrations of pollutants—CO, NO₂, SO₂, HCHO, and O₃ were analyzed from 2018 to 2023. The study identified annual and seasonal variations in pollutant levels and mapped pollutant hotspots. Additionally, it investigated how different urban growth patterns like infilling, edge expansion, and leapfrog development impact air quality. Results indicate that Leapfrog development significantly increases NO2 (1.46), SO2 (1.70), and HCHO (1.70) concentrations by 28.91%, while infilling impacts CO (1.58) and NO2 (0.88). Edge expansion has a lower impact, significantly affecting O3 (0.92), indicating varying pollutant contributions across urban growth patterns.